Effects of inventory turnover, total asset turnover, fixed asset turnover, current ratio and average collection period on profitability - MARY IVANA SUNJOKO; ERIKA JIMENA ARILYN (Jurnal Bisnis dan Akuntansi, 2016)
The purpose of this research is to empirically examine the effect of Inventory Turnover, Total Assets Turnover, Fixed Assets Turnover, Current Ratio and Average Collection Period on profitability. Sample of this research are pharmaceutical companies listed at Indonesia Stock Exchange period 2007 – 2013. The research findings can be summarized as follow, Fixed Asset Turnover and Current Ratio affect profitability, while Inventory Turnover, Total Asset Turnover and Average Collection Period do not affect profitability